Destination elsewhere : displaced persons and their quest to leave postwar Europe - Balint, Ruth 2005- (Cornell University Press, 2021)
"This book examines the efforts and experiences of displaced persons after the Second World War to leave Europe for resettlement through the International Refugee Organisation, and the creation of new categories of legitimacy for refugees as immigrants in this period"--